Transesterification and purification of biodiesel from waste cooking oil - Ngu, Ai Ling (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
In this study, the level of free fatty acids in used oil are low at 0.73 %, hence, single stage transesterification was sufficient. Two process variables that been investigated were the molar ratio of methanol-to oil and the amount of catalyst, KOH. The variables that were fixed throughout the whole experiment were the reaction time, 90 minutes, reaction temperature, 55 °C and mixing degree of mechanical stirrer at 1200 rpm. The results show the highest biodiesel production, which reached 98 % of biodiesel is 9:1 molar ratio of methanol-to-oil with 0.5 wt % catalyst. Besides, this paper also studied on the purification of biodiesel through distilled water washing method to produce high purity biodiesel. Biodiesel purification was carried out by washed the biodiesel with different volume of distilled water with respect to the biodiesel at temperatures below 60 °C and 1200 rpm agitation. Results show 15 % (v/v) distilled water to produce high purity biodiesel with a low saponification number, 211775 mg/g. To commercialize the product, a conceptual design of the production plants has been done with the SuperPro designer software to evaluate the economic assessment of the product. From SuperPro, the selling price of the methyl ester (biodiesel) is RM 2.30/liter.